Exploratory study of DeFi oracles: trust models, economics and security - Wong, Jiawen (Nanyang Technological University, 2024)
Given the rapid development of blockchain technology, decentralized finance (DeFi) is a field that is expanding quickly too. Oracles play a key role in this area by bridging the gap between blockchain and external data sources. Despite their critical role, the intricacies of oracle networks are often underexplored. This report aims to delve into oracle networks through several lenses, such as their taxonomy, trust models, economic considerations, and security mechanisms. In doing so, it hopes to be of use for further research and innovation. Through the combination of academic papers and grey literature, as well as an examination of various oracle networks, this report aims to shed light on the various components and functions of oracle networks within the DeFi ecosystem.